ISLAMIC EDUCATION AND THE MULTICULTURAL SOCIETY: DESCRIPTION OF EDUCATION FOR CULTURAL DIVERSITY IN TWO ISLAMIC SCHOOLS IN INDONESIA - Raihani Raihani (Universitas Islam Negeri Alauddin Makassar, 2014)
Generally, educational practices in two Islamic schools, contained teachings of religious and cultural diversity. The two schools are located in two different urban areas – Yogyakarta and Palangkaraya– each of which has interesting characteristics as multicultural cities. Considering that Islamic schools can contribute to the creation of multicultural society in Indonesia, in contrast on an assumption that Islamic schools are religious schools, which in theories contribute to the segregation of society by imposing students to the truth claim belief and behaviours. Students of religious schools nurture in themselves a belief that only their religion is true and others are false. Consequently, as this assumption goes on, students act to show their religion’s superiority to others. Even if they can demonstrate tolerance to other religious followers and practices, the social segregation is established, and becomes potential frictions among different religious people. In addition, Islamic schools are often described as backward and monolithic religious schools, which cannot accept different religions and interpretations to the Islamic teachings.